RESULTS OF THE PEDAGOGICAL EXPERIMENT ON THE FORMATION OF FUTURE BORDER GUARD OFFICERS’ PROFESSIONAL CULTURE - Шумовецька, С. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article reveals the topicality of the investigation into the issues of professional culture formation in respect of its importance for a border guard officer as well as for the proper organization of their daily and operational activities of the border unit. The purpose of the article is to cover the results of the experimental verification of the concept and technology of border guard officers’ professional culture formation in a higher military educational institution. The use of general scientific and specific methods of theoretical and empirical research, primarily analysis of scientific literature on the problem, systematization and generalization of materials, logical and systematic approaches, allowed to outline the pedagogical essence of the key concepts of the study, to characterize the conceptual foundations of the formation of future border guard officers’ professional culture. The future border guard officers’ professional culture formation concept, which is a set of interrelated rules, principles, ideas and methods concerning border guard officer's professional culture formation that is revealed at three levels: methodological, theoretical and technological, is explained in detail. The basic nature of the technology, which presupposes future border guard officers’ professional culture formation is developed. Each of these stages corresponds to the training course, including the familiarization, formation, actualization and individualization stages. The main directions of pedagogical influence during all four stages, first of all, on the formation of motivation to the study of the border guard officers’ professional culture; the development of cadets' communicative skills necessary for professional communication with citizens at the state border crossing points; the interpersonal interaction skills improvement by means of problem-based communication training; stimulation of cadets’ cognitive activity by means of problem-based learning methods; extending knowledge on the issues of leadership and border management through research methods; organizing a special optional course aimed at familiarizing cadets with the border guard service values, history of border service and Ukrainian-Russian relations, etc., are described. The data confirming the necessity and expediency of introducing the future border guard officers’ professional culture formation technology at a higher military educational institution are provided. In addition to the above, the methodological recommendations for scientific and pedagogical executives on border guard officers’ professional culture formation are offered.